Temperature modulates immune gene expression in mosquitoes during arbovirus infection. Issue 1 (6th January 2021) - Wimalasiri-Yapa, B. M. C. Randika; Barrero, Roberto A.; Stassen, Liesel; Hafner, Louise M.; McGraw, Elizabeth A.; Pyke, Alyssa T.; Jansen, Cassie C.; Suhrbier, Andreas; Yakob, Laith; Hu, Wenbiao; Devine, Gregor J.; Frentiu, Francesca D.
Abstract : Abstract : The principal vector of dengue, Zika and chikungunya viruses is the mosquito Aedes aegypti, with its ability to transmit pathogens influenced by ambient temperature. We use chikungunya virus (CHIKV) to understand how the mosquito transcriptome responds to arbovirus infection at different ambient temperatures. We exposed CHIKV-infected mosquitoes to 18, 28 and 32°C, and found that higher temperature correlated with higher virus levels, particularly at 3 days post infection, but lower temperature resulted in reduced virus levels. RNAseq analysis indicated significantly altered gene expression levels in CHIKV infection. The highest number of significantly differentially expressed genes was observed at 28°C, with a more muted effect at the other temperatures. At the higher temperature, the expression of many classical immune genes, including Dicer-2, was not substantially altered in response to CHIKV. The upregulation of Toll, IMD and JAK-STAT pathways was only observed at 28°C. Functional annotations suggested that genes in immune response and metabolic pathways related to energy supply and DNA replication were involved in temperature-dependent changes. Time post infection also led to substantially different gene expression profiles, and this varied with temperature. In conclusion, temperature significantly modulates mosquito gene expression in response to infection, potentially leading to impairment of immune defences at higher temperatures.